Effectiveness of Conciliation and Arbitration in the Ferro- Chrome Industry in Zimbabwe - Watadza, Christopher; Mahapa, Mildred; Muchadenyika, Chakanaka Ernest (European Scientific Journal, ESJ, 2016)
The study sought to establish the effectiveness of Conciliation and Arbitration as dispute resolution mechanism with the case of Ferro –Alloy Industry in Zimbabwe. A case study of 2 major players in the industry were examined in a descriptive research design. Backing the research is the concept of legal pluralism which then defined conciliation and arbitration as alternative dispute resolution systems. Management and Trade Union representatives, general employees and Labour Officers participated through interviews. The research uncovered that the current legal framework was not providing a conducive and enabling regulatory environment to ensure an effective dispute resolution mechanism. The gaps in terms of time limits, the absence of explicit guidelines on conciliation, lack of finality to arbitral awards were identified as major drawbacks of the current legal structure. The State department, the Ministry of Labour, is the vehicle for an effective dispute resolution mechanism. The research identified that the department was inadequately resourced to enable speedy and prompt resolution of disputes. Due to the centrality and inevitability of disputes at workplace, the research recommended that government should amend the current legal framework to align it to International Labour Organisations provisions on conciliation and arbitration to ensure an effective resolution to disputes.